FRAUD HUNTERS AROUND THE WORLD: FIGHTING DECEPTION IN DIFFERENT COUNTRIES - Mihus, Iryna (Socio-economic relations in the digital society, 2025)
As financial fraud grows more sophisticated and global in scope, countries have developed diverse mechanisms to detect, investigate, and prosecute fraudulent activities. This article presents a comparative analysis of fraud-hunting institutions in seven countries: the United States, the United Kingdom, China, India, Germany, Nigeria, and Brazil. It explores the structure, powers, and operational strategies of government agencies and private auditors tasked with combating fraud, including the use of artificial intelligence, digital forensics, and inter-agency cooperation. The study draws on landmark investigations – such as the Enron scandal, LIBOR manipulation, the Wirecard collapse, and Brazil’s Operation Car Wash – to highlight differences in institutional responses, transparency, and whistleblower protection. While advanced economies benefit from robust regulatory oversight and legal safeguards, emerging markets face challenges such as limited forensic capacity, political interference, and weaker protections for informants. Despite these differences, there is a global trend toward enhanced technological tools and cross-border enforcement collaboration. The analysis concludes that no single model guarantees success. Instead, effective anti-fraud efforts rely on a combination of legal authority, institutional independence, technological integration, and political will to act decisively against financial misconduct.